Food and environment in early and medieval China - Anderson, E. N., 1941- (Encounters with Asia., 2014)
"Food and Environment in Early and Medieval China traces the development of the food systems that coincided with China's emergence as an empire. Before extensive trade and cultural exchange with Europe was established, Chinese farmers and agriculturalsits developed systems that used resources in sustainable and efficient ways, permitting intensive and productive techniques to survive over millenia. Fields, gardens, semiwild lands, managed forests, and specialized agricultural landscapes all became part of an integrated network that produced maximum nutrients with minimal input--though not without some environmental cost"--Jacket